2007
DOI: 10.3934/dcdsb.2007.8.389
|View full text |Cite
|
Sign up to set email alerts
|

Detecting perfectly insulated obstacles by shape optimization techniques of order two

Abstract: The paper extends investigations of identification problems by shape optimization methods for perfectly conducting inclusions to the case of perfectly insulating material. The Kohn and Vogelius criteria as well as a tracking type objective are considered for a variational formulation. In case of problems in dimension two, the necessary condition implies immediately a perfectly matching situation for both formulations. Similar to the perfectly conducting case, the compactness of the shape Hessian is shown and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Among all of them, shape optimization methods (see e.g. [3,18,32]) present interesting features: in particular, they are easily adaptable to problem governed by a different partial differential equation, such as Stokes system (see e.g. [5,20,22,33]), and obstacle characterized by different limit conditions, such as Neumann or generalized boundary conditions (see e.g.…”
Section: Page 87])mentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of them, shape optimization methods (see e.g. [3,18,32]) present interesting features: in particular, they are easily adaptable to problem governed by a different partial differential equation, such as Stokes system (see e.g. [5,20,22,33]), and obstacle characterized by different limit conditions, such as Neumann or generalized boundary conditions (see e.g.…”
Section: Page 87])mentioning
confidence: 99%
“…We do so through the minimization of a Kohn-Vogelius functional, which will have both the shape of ω * and the unknown data as variable, since such type of functional has already been used successfully to solve obstacle problems and data completion problem separately (see e.g. [6,3]).…”
Section: Remark 12mentioning
confidence: 99%
“…This method is used e.g. in the work [1] of Afraites et al (where a regularization by parameterization is used). Note that the standard algorithm based on shape derivatives moving the mesh does not provide the opportunity to change the topology of the shape and consequently the number of inclusions has to be known in advance.…”
Section: Flip Procedures In Approximation Of Multiple-component Shapesmentioning
confidence: 99%
“…Detailed studies including regularity estimates showed that if the domain is C 2,α and the perturbation is a C 2,α diffeomorphism then the Hessian is coercive at the minimum, but with respect to a weaker norm [12,11]. The detection of obstacles for the conductivity equation using second order shape optimization was proposed in a series of work [15,1,2] under various hypotheses regarding the obtacle: perfectly insulating, perfectly conducting, having a different conductivity. Another series of work adressed electromagnetic shaping, and the explicit computation of the Hessian that is affordable using a boundary integral method to estimate the solutions of the equation [22,24].…”
Section: Introductionmentioning
confidence: 99%